CREATE A LOCAL INTELLIGENCE-BASED LEARNING ENVIRONMENT - Ignatius Septo Pramesworo; Erna Widyasari; Sigit Haryanto; Mohammad Ahmad Bani Amer (Adisam Publisher, 2024)
The research aims to explore the development and application of a local wisdom-based learning environment in the context of modern education. By adopting a qualitative approach, the study examines various strategies and methodologies for integrating local values, practices, and knowledge into the school curriculum, as well as identifying their impact on student learning experiences. Research results show that integrating local wisdom into education not only enriches curricula but also improves the relevance and contextualization of learning, facilitating critical thinking, creativity, and intercultural understanding among students. In addition, this approach supports the preservation of local culture and the promotion of diversity. This research suggests that to effective implementation, it requires teacher training, development of learning resources, and active involvement of the local community. Therefore, the importance of creating a local wisdom-based learning environment thus holds significant potential in improving the quality of education and preparing students with relevant capabilities to face global challenges with a strong local perspective.